P012 A process evaluation of an incentivized home-based intervention to test and start (HITS) in rural kwazulu-natal, south africa. (14th July 2019) - Adeagbo, Oluwafemi; Tanser, Frank; Gumede, Velaphi; Mathenjwa, Thulile; Matthews, Philippa; Wyke, Sally; Bärnighausen, Till; Pillay, Deenan; Mcgrath, Nuala; Blandford, Ann; Seeley, Janet; Shahmanesh, Maryam
Abstract : Background: Despite freely available HIV testing and treatment, many men do not access HIV treatment and care in South Africa. We conducted home-based intervention to test and start (HITS) - a factorial design randomised controlled trial (ClinicalTrials.gov #NCT03757104 ). HITS is designed to assess the effectiveness of two financial micro-incentives (R50[$3] food vouchers) for home-based HIV testing and, following a HIV-positive test, to link to HIV care; and/or a male-targeted counselling application to support home-based testing (EPIC-HIV1) and to support men linking to care (EPIC-HIV2). The research was conducted in an HIV-hyperendemic setting in rural KwaZulu-Natal. Methods: We conducted a process evaluation to understand the impact of HITS intervention on the decision of men to test for HIV and/or engage in HIV care. Thirty men (16–73 years) were purposively selected in the three intervention arms (ten per arm) and interviewed between August and December 2018. Emerging themes were thematically analysed following an interpretivist approach. Results: Although participants welcomed the male-centred intervention, some felt that the voucher amount was too small. Overall, many participants described the voucher, EPIC-HIV, and the convenience and privacy of home-based testing as 'catalysts' to test or link to care irrespective of their reported intrinsic motivations to know their status or concerns around HIV related sexual risk behaviours. One-third of the interviewees were first-time testers. Despite the incentives, two out of the five men who tested positive reported that they have not linked to care because they feared stigmatisation at local clinics. Conclusion: Generally, the HITS intervention influenced men's motivation to test and access care, but some respondents felt the incentive was insufficient to overcome some barriers of accessing HIV care at fixed clinics. To achieve the 90–90–90 targets among men in our setting, provision of decentralised, non-judgmental and convenient incentivised HIV care services could increase uptake of HIV testing and treatment. Disclosure: No significant relationships.